Oral Antibiotics Reduce Intestinal Necrosis in Acute Mesenteric Ischemia: A Prospective Cohort Study. (February 2019) - Nuzzo, Alexandre; Maggiori, Leon; Paugam-Burtz, Catherine; Cazals-Hatem, Dominique; Ronot, Maxime; Huguet, Audrey; Becq, Aymeric; Castier, Yves; Weiss, Emmanuel; Plessier, Aurélie; Tran-Dinh, Alexy; Joly, Francisca; et al.
Abstract : OBJECTIVES: To identify treatments likely to prevent progression towards irreversible transmural intestinal necrosis (ITIN) in acute mesenteric ischemia (AMI). METHODS: Prospective observational cohort study from a French intestinal stroke center. Multivariate analysis using a time-dependent Cox regression model. RESULTS: Between 2009 and 2015, 67 patients with AMI were included. ITIN occurred in 34% of patients and mortality was 13%. Oral antibiotics was independently associated with a decreased risk of ITIN (HR: 0.16 (95% CI = 0.03–0.62); p  = 0.01). CONCLUSIONS: By decreasing luminal bacterial load and translocation, oral antibiotics in addition to early revascularization might reduce progression of AMI to ITIN.